Representing Orality: Scott’s The Lay of the Last Minstrel and Conjectural History - Regan, John (Romanticism and Victorianism on the Net, 2011)
This article contextualizes Walter Scott's The Lay of the Last Minstrel in relation to an Edinburgh literary milieu influenced by some the most famous progenitors of Scottish Enlightenment historical theory. After a preliminary survey of the intellectual landscape out of which Scott's poem comes, the discussion is orientated specifically around the influence, on Scott, of Adam Ferguson's seminal conjectural history, the Essay on the History of Civil Society. Oral poetry is integral to Ferguson's nuanced deteriorationist narrative of human development, and it is my central contention that The Lay is the apotheosis of a Romantic anxiety over the representation of preliterary verse. This article's primary area of interest is not the poetry of The Lay itself but the discourses of history, historicity, verse and versification to which Scott, Adam Ferguson, Francis Jeffrey and several others contributed before, during and after the poem's publication.